Simultaneous Impact of Hollow Droplet and Continuous Dense Droplet on Liquid Film - Li, Dashu; Liang, Gangtao; Hua, Dan (Frontiers in Energy Research, 2022)
The Simultaneous impact of a hollow droplet and a continuous dense droplet on a liquid film was investigated using the coupled level set and volume of fluid (CLSVOF) method. Analyses included fluid dynamics and heat transfer characteristics in impact. Results showed that the interfacial phenomena after impact incorporates spreading, central jet between droplets, edge liquid sheet, and counter jet inside the hollow droplet. The pressure gradient is the major cause for the above phenomena. The significant parameter of impact velocity is closely related to the dynamics and heat transfer for droplets impacting on a liquid film. Droplets with higher impact velocity exhibit a greater spreading factor, central jet height, edge jet height, and counter jet height. Besides, wall heat flux increases more notably for droplets with a higher impact velocity. Compared with the continuous droplet, the hollow droplet shows a smaller spreading factor and edge jet height, a higher wall heat flux, but a narrow thermally affected region. This study provides a fundamental understanding for the application of high-pressure spray combustion.